Field-reversal versus self-reversal hypothesis: The Ti-rich titanomagnetite bearing basalts and their partly self-reversed partial thermoremanent magnetization induced in the laboratory field - ORLICKÝ, Oto (Contributions to Geophysics and Geodesy, 2021)
Three Ti-rich titanomagnetite bearing samples were subjected to inducing of the thermoremanent magnetization in the laboratory field of normal polarity and the intensity of about H = 50 μT. The high vacuum of about 10–4 to 10–5 Torr., was used during heating and cooling of the samples, to prevent an oxidation of original Ti-Mt-es. The original basalt and two artificial samples acquired intense PTRM, and an orientation of the total vector of the PTRM was antiparallel (reversed) with respect to the H component of the magnetizing field, but the inclination of the PTRM was of positive sense. The results have proven that in all three samples only non-complete, partly self-reversed PTRM was acquired during the laboratory inducing in the field of normal polarity. The original Ti-rich titanomagnetites were partly oxidized, despite the highly evacuated space, which is the primary cause for a non-complete self-reversal magnetization of samples during the experiment.